Energy storage for electricity generation and related processes: Technologies appraisal and grid scale applications - Argyrou, Maria C.; Christodoulides, Paul; Kalogirou, Soteris A. (My University, 2018)
Renewable Energy Sources have been growing rapidly over the last few years. The spreading of renewables has become stronger due to the increased air pollution, which is largely believed to be irreversible for the environment. On the other hand, the penetration of renewable energy technologies causes major problems to the stability of the grid. Along with the fluctuations of the renewable energy technologies production, storage is important for power and voltage smoothing. Energy storage is also important for energy management, frequency regulation, peak shaving, load leveling, seasonal storage and standby generation during a fault. Thus, storage technologies have gained an increased attention and have become more than a necessity nowadays. This paper presents an up to date comprehensive overview of energy storage technologies. It incorporates characteristics and functionalities of each storage technology, as well as their advantages and disadvantages compared with other storage technologies. Comparison tables with several characteristics of each storage method are included, while different applications of energy storage technologies are described as well. Finally, several hybrid energy storage applications are analyzed and different combinations of energy storage technologies are reviewed.
Keywords: Energy storage; Renewable energy; Comparison; Grid; Applications; Hybrid storage